2022
DOI: 10.3390/ijms232314574
|View full text |Cite
|
Sign up to set email alerts
|

IL-6 and IL-8: An Overview of Their Roles in Healthy and Pathological Pregnancies

Abstract: Interleukin-6 (IL-6) is an acknowledged inflammatory cytokine with a pleiotropic action, mediating innate and adaptive immunity and multiple physiological processes, including protective and regenerative ones. IL-8 is a pro-inflammatory CXC chemokine with a primary function in attracting and activating neutrophils, but also implicated in a variety of other cellular processes. These two ILs are abundantly expressed at the feto-maternal interface over the course of a pregnancy and have been shown to participate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
35
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 67 publications
(36 citation statements)
references
References 362 publications
0
35
0
1
Order By: Relevance
“…Infections or inflammatory conditions, such as COVID-19 during pregnancy, can have a detrimental impact on fetal development and also contribute to pregnancy-associated pathological conditions ( 34 ). Despite the conflicting data regarding the overall profile of IL-6, TNF-α and IFN-γ during healthy pregnancy, there is a consensus that the establishment of a pro-inflammatory microenvironment is associated with the risk of developing pregnancy-associated pathological conditions, including pregnancy loss, preeclampsia, and gestational diabetes mellitus ( 35 ). In this sense, the upregulation of pro-inflammatory cytokines in pregnant women with convalescent COVID-19 may suggest that these patients are more vulnerable to developing adverse pregnancy outcomes.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Infections or inflammatory conditions, such as COVID-19 during pregnancy, can have a detrimental impact on fetal development and also contribute to pregnancy-associated pathological conditions ( 34 ). Despite the conflicting data regarding the overall profile of IL-6, TNF-α and IFN-γ during healthy pregnancy, there is a consensus that the establishment of a pro-inflammatory microenvironment is associated with the risk of developing pregnancy-associated pathological conditions, including pregnancy loss, preeclampsia, and gestational diabetes mellitus ( 35 ). In this sense, the upregulation of pro-inflammatory cytokines in pregnant women with convalescent COVID-19 may suggest that these patients are more vulnerable to developing adverse pregnancy outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Our data also demonstrated that IL-6 and CXCL8 were included in the set of attributes acquiring strong correlation in the 3 rd pregnancy trimester, named COVID-selective correlations. Implications of IL-6 and CXCL8 in pregnancy-associated pathological conditions, such as pregnancy loss, preeclampsia, gestational diabetes mellitus, and infection/inflammation have been reported ( 35 ). These two soluble mediators are abundantly produced at the feto-maternal interface throughout pregnancy and have been shown to participate in several pregnancy-related events.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The review of Vilotić et al [ 3 ] provided a comprehensive overview on the role of IL-6 and IL-8, inflammatory cytokines, in cycling endometrium, the feto–maternal interface, establishment of pregnancy, parturition, and in the pathogenesis of pregnancy-related complications such as pregnancy loss, preeclampsia, gestational diabetes mellitus and infection/inflammation.…”
mentioning
confidence: 99%